TEACHINGS OF JESUS A.S. IN QURAN AND CONTEMPORARY CHRISTIANITY - Abdul Hameed Arain; Mukhtiar Khandro (دی اسکالر)
After the demise of Prophet Moses A.S Jews declined morally and religiously. Shortly, Almighty Allah blessed them with a Prophet Jesus A.S with his religious book “Gospel” for their guidance. As Prophet Jesus departed from this world, his followers distorted his teachings; even they adopted those things which the prophet strictly prohibited. In the last holy book Quran, Almighty Allah not only affirmed the earlier prophets but also declared their true teachings. Likewise, Almighty Allah stated the true teachings of Prophet Jesus.  This article discusses the teachings of Jesus which are mentioned in holy Quran and it also examines the current believes of Bible to  analyzed what were the real teachings of prophet Jesus and what amendments were brought in it.